2010
DOI: 10.1590/s0366-69132010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades mecânicas de materiais compósitos à base de cimento Portland e resina epoxi

Abstract: ResumoO estudo de materiais de alto desempenho e multifuncionais, como os compósitos poliméricos cimentícios, tem sido o foco de inúmeras pesquisas na indústria da construção civil. Este trabalho investiga o efeito da combinação de uma fase polimérica termorrígida, uma resina epóxi, com cimento Portland branco estrutural, seguido da avaliação da resistência à compressão e módulo de elasticidade. Este compósito, quando comparado individualmente com as suas matérias-prima originais, promove um aumento da resistê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 9 publications
1
27
0
5
Order By: Relevance
“…Therefore, the amount of hydration products, the hydrate crystals morphology and the microstructure of cement paste are modified. It is related to the partial intercalation of the polymer chains within the cement hydration products and interactions obtained by hydrogen bonds between the resin and these products ,. Moreover, bulk density of cement tends to decrease by increasing epoxy resin content according to the mixing rule of the present phases (polymer and cement) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the amount of hydration products, the hydrate crystals morphology and the microstructure of cement paste are modified. It is related to the partial intercalation of the polymer chains within the cement hydration products and interactions obtained by hydrogen bonds between the resin and these products ,. Moreover, bulk density of cement tends to decrease by increasing epoxy resin content according to the mixing rule of the present phases (polymer and cement) .…”
Section: Introductionmentioning
confidence: 99%
“…2017 367 The use of particulate composites as reinforcement for timber beams has also been investigated in the literature. BRAZ et al (2013) have reported the use of a polymer-ceramic blend (PANZERA et al, 2010) to repair the compressive zone of timber beams. The finite element analysis (FEA) has pointed out the polymer-cementitious blend as an alternative solution for reinforcement of timber beams, presenting excellent strength and stiffness properties in compression.…”
Section: Introductionmentioning
confidence: 99%
“…A thermoset polymer phase has also been added to enhance the mechanical properties of cementitious composites. PANZERA et al (2010) have evaluated the effect of the epoxy polymer combined with the white Portland cement. The incorporation of 50wt% (weight fraction-wt%) of epoxy polymer into a Portland cement paste resulted in superior mechanical properties compared to the reference condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the presence of the polymeric phase leads to an increase of strength and a reduction of the bulk density, compared to pure cement. Based on FTIR analysis it was observed that the formation of hydrated cement grains can occur due to the presence of epoxy resin 10 . Panzera et al 11 also investigated the effect of adding thermoset polymer (25, 50 and 75 wt.…”
Section: Introductionmentioning
confidence: 99%